Leveraging Artificial Intelligence in Supporting Remote Information Technology Project Management: A Systematic Literature Review - Prasetyo, Seto Adhi; Raharjo, Teguh; Fitriani, Anita Nur (Dinasti Research, 2026)
The transition to remote IT project management presents unique challenges in collaboration, resource allocation, and adaptability. While Artificial Intelligence (AI) is increasingly demanded as a strategic enabler to manage these complexities, its specific application within remote IT environments, particularly through the principles-based PMBOK7 framework, remains underexplored. To address this literature gap, this study presents a Systematic Literature Review (SLR) analyzing peer-reviewed literature published between 2021 and 2026. The review identifies 11 empirically validated studies and extracted 8 unique AI implementations, namely machine learning, natural language processing, neural network, multi-agent systems, large language model, fuzzy logic, genetic algorithm, and probability graph models. These technological implementations are systematically mapped across the eight PMBOK7 performance domains and five primary areas of change in remote IT work. The findings indicate that while empirical AI implementation in this domain is still in its infancy, it fundamentally enhances aspects like stakeholder communication, team flexibility, data-driven project planning, and holistic view of the project for project managers. Ultimately, this study serves as a foundational stepping stone for global IT organizations transitioning toward AI-assisted distributed project management